Las juntas de acción comunal y la gestión pública en Colombia (2019)
The present article approaches in a reflexive way the role of the third sector in the state work, with special emphasis, of theoretical and juridical character, in the communal action boards, in the case of Colombia, as organizations belonging to that sector, which contribute to public management through the promotion of community and citizen participation, to finally critically review the role of the boards of the municipality of Tunja Boyacá Colombia